2017
DOI: 10.1038/bmt.2017.243
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HLA-G polymorphism on the outcome of allogeneic hematopoietic stem cell transplantation for metastatic renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) is particularly sensitive to immune intervention. HLA-G, a non-classical HLA class I molecule with immunomodulatory properties, has been studied with regard to outcome after hematopoietic stem cell transplantation (HSCT), in particular the 14 bp insertion/deletion polymorphism in the 3' untranslated region. Here we analyzed n=56 patients affected by metastatic RCC who received an allogeneic HSCT between 1998 and 2006 in Milano, Marseille, Clermont-Ferrand and Stockholm. The 14 bp pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In the context of allogeneic hematopoietic stem cell transplantation (HSCT), it has been shown that patients with better outcome carried 14-bp DEL/DEL and 14-bp INS/DEL genotypes, suggesting 14-bp INS/DEL genotype as potential biomarker of transplantation outcome (32,33). Overall, the association between 14-bp INS/DEL genotypes and disease susceptibility provided some positive, but not conclusive, association.…”
Section: Hla-g Genetic Footprint and Correlation With Disease Coursementioning
confidence: 99%
“…In the context of allogeneic hematopoietic stem cell transplantation (HSCT), it has been shown that patients with better outcome carried 14-bp DEL/DEL and 14-bp INS/DEL genotypes, suggesting 14-bp INS/DEL genotype as potential biomarker of transplantation outcome (32,33). Overall, the association between 14-bp INS/DEL genotypes and disease susceptibility provided some positive, but not conclusive, association.…”
Section: Hla-g Genetic Footprint and Correlation With Disease Coursementioning
confidence: 99%
“…However, no concordant results could be observed regarding pregnancy loss, autoimmune diseases or cancer (Jiang et al., 2019; Kim et al., 2015; Li et al., 2015; Monti et al., 2019). As for the impact of HLA‐G in haematopoietic stem cell transplantation, 14 bp INS/DEL and 14 bp DEL/DEL haplotypes were reported to be transplantation markers for better outcomes (Chiusolo et al., 2012; Crocchiolo et al., 2018).…”
Section: Nonclassical Hla Moleculesmentioning
confidence: 99%
“…There are studies showing the impact of genotyping and matching for non-classical HLA (including HLA-E, HLA-G or MICA/B loci) on HSCT outcome, including manifestation of cGvHD (reviewed in ( 46 , 59 , 60 ), and the role of anti-MICA antibodies in organ transplant recipients. Therefore, non-classical HLA molecules should also be considered as potential targets of alloantibodies in HSCT recipients.…”
Section: Alloantibodies and Gvhdmentioning
confidence: 99%